A Geographical analysis for mine distribution and its impact on natural pasture in Sulaymaniyah government. (Raparin Journal of Humanities (RJH), 2023)
Mine is identified as a part of war and intimidating weapon for people. It is a war weapon which is used for the purpose of disserving both physical and material damages. It is the most effective and the cheapest weapon which is designed to be placed under a material or under the ground near the surface of the natural pastures that are not useful for the purpose of cultivating and farming due to some natural factors such as (topography, climate, soil, etc.) of the lands which covered with forests and grasslands because of the diversity of the places, the types and the variability of the seasons which grow up without any human efforts. The lands that are the main sources of the best, healthiest, and cheapest kinds of fodders and algae for all domestic and wild animals. Natural pastures are also renewable resources that have influence on all the aspects of geographical, environmental, economic, social, etc. of each regions. The study attempts to show the distribution of minefields in Sulaymaniyah province, the history of mines in the study area, and their effects on natural pastures in the Sulaymaniyah province. Some factors in the study area cause an increase in mines; the study attempts to show the distribution of minefields in the Sulaymaniyah province to protect people, tourists, and livestock owners in the border region in particular. In the study, inductive, regional, and analytical methods are used. The study consists of three main parts: the first is about the site and situation of Sulaymaniyah province; the second is about the types of mines and the distribution of minefields in the Kurdistan region and Sulaymaniyah province. The last part is about the effect of mines on the natural pastures in the study area, with a conclusion and suggestion to reduce the impacts of mines on the natural pastures and their people in Sulaymaniyah province in general. At the end of the study, some results were obtained, such as: Sulaymaniyah province has the highest rate of landmines, which is about %64 of all landmines included in the Kurdistan region, and about %84 of landmines in Sulaymaniyah province are located in districts that have borders with Iran, because of the Iraq-Iran war. In the study area, minefields have an impact of about %4.11 on natural pastures, and about %64.43 of the livestock wealth in Sulaymaniyah province depends on natural pastures.